A meaningful everyday life experienced by adults with acquired neurological impairments: A scoping review. - Lena Aadal; Michele Offenbach Hundborg; Hanne Pallesen; Randi Steensgaard (PLoS ONE)
Objective This scoping review explores the characteristics of a meaningful life appraised by adults living with an acquired neurological impairment. Introduction Limitations in function, activity or participation following a neurological injury or disease imposes comprehensive changes on the every-day life of the affected person and close relatives. Including patients' perception of a meaningful life is pivotal to facilitate motivation and individualize rehabilitation efforts to address the patients' wishes, hopes, needs, and preferences. Surprisingly, only little research has been devoted to illuminating what a meaningful life is from the impaired person's perspective. Hence, a scoping review of existing knowledge is needed to facilitate person-centered high-quality rehabilitation and research initiatives. Inclusion criteria All studies, published in English or Scandinavian languages describing a meaningful life as experienced by adult persons with neurological impairment were included. No search date range filter was selected. Methods This review followed the Joanna Briggs Institute (JBI) methodology for scoping reviews according to a published protocol. A three-step search strategy was conducted in the databases PubMed, Cinahl, PsycINFO and Embase. At least two independent researchers conducted inclusions and exclusions, data extraction, and analyses. Covidence software was used to manage the information. Findings We identified 307 studies. Of these, 20 were included and quality assessed. Findings are reported in accordance with the PRISMA- SCR checklist and descriptively presented mapped in three main domains and 10 ten sub-domains. Conclusion Current literature conveys no clear definition or perception of what a meaningful life is. However, across the 20 included studies, the following main characteristics were stepped forward as particularly significant for adults living with an acquired neurological impairment in regard to achieving a meaningful life: i) to be part of meaningful relationships and meaningful activities; ii) to become confident with one's perceived identity.